CTX-M-15 and OXA-10 beta lactamases in multi drug resistant Pseudomonas aeruginosa: First report from Pakistan. (April 2017) - Ullah, Waheed; Qasim, Muhammad; Rahman, Hazir; Khan, Saadullah; Rehman, Zia ur; Ali, Nawab; Muhammad, Noor
Abstract: Background: Pseudomonas aeruginosa is an emerging threat to public health worldwide due to their rapid development of drug resistance including beta-lactamases. The present study was designed to investigate the incidence of β-lactamases and genotypic pattern of CTX and OXA in the clinical isolate of multidrug resistant P. aeruginosa. Methods: In this study a total of 102 MDR P. aeruginosa isolates obtained from Lady Reading Hospital, Peshawar, Pakistan were subjected to extended spectrum beta lactamase (ESBL), metallo beta lactamase (MBL) and plasmid mediated β-lactamase (AmpC) detection using phenotypic and molecular methods. Furthermore, sequencing of CTX and OXA gene was performed. Results: Out of 102 MDR P. aeruginosa isolates, 71 (69.6%) were beta lactamase producers. The incidence of ESBL, MBL and AmpC in clinical isolates of P. aeruginosa was found to be 23.94%, 40.84% and 35.21% respectively. Co-production of ESBL and AmpC were also observed in some isolates. There were 14 (19.71%) CTX-M-15 harboring isolates which were ESBL (64.28%), MBL (21.42%) and AmpC (14.28%) producer. Co-production of ESBL/MBL (14.28%), ESBL/AmpC (14.28%) and MBL/AmpC (14.28%) were also observed in the CTX M-15 harboring isolates while 12.28% isolates were not ESBL, MBL or AmpC producer. OXA-10 was detected in 8 (11.26%) isolates which were ESBL (12.5%), MBL (37.5%) and AmpC (12.5%) producer. OXA 10 isolates also exhibit co-production of ESBL/AmpC (12.5%) and MBL/AmpC (12.5%). All CTX-M-15 carried the class A β-lactamase conserved domain while OXA-10 harbored conserved domain of class D β-lactamase. Conclusion: The current study for the first time reported and characterized the CTX-M-15 and OXA-10 among MDR P. aeruginosa isolates from Pakistan. Further efforts are needed to understand the molecular mechanism of drug resistance with CTX and OXA harboring P. aeruginosa isolates. Highlights: Out of 102 MDR P. aeruginosa isolates, screened for ESBL, MBL and AmpC, 69.6% were beta lactamase producers. Among these 19.71% isolates were harboring CTX-M-15 and in 11.26% isolates, OXA-10 was found and there were ESBL, MBL or AmpC producers. Co-production of ESBL/MBL, ESBL/AmpC and MBL/AmpC was also documented. All CTX-M-15 carried the class A β-lactamase conserved domain while OXA-10 harbored conserved domain of class D β-lactamase. CTX-M-15 and OXA-10 among MDR P. aeruginosa isolates are first time reported from Pakistan.